Refractory ischaemic priapism following the concomitant use of Viagra and cocaine: a case report - Kugblenu, Jomo; Idedevbo , Edore; Eche, Eric; Eltawagny, Mahmoud; Adesokan, Adedapo M. (Journal of Global Medicine, 2024)
Introduction: Ischaemic priapism is a urological emergency which drugs, sickle cell disease, haematological dyscrasias, and neoplastic syndromes may cause. We report a case of a 48-year-old male who presented with refractory ischaemic priapism following the concomitant use of recreational Viagra and cocaine. Case Report: A 48-year-old man presented to the Emergency Department (ED) with painful sustained priapism for 24 h, following Viagra and cocaine usage. Initial treatment of ejaculation and cold compresses did not help at home for 24 h. At a presentation in the ED, there was failed penile aspiration and injection of sympathomimetic, intracavernosal adrenoceptor agonist Phenylephrine was to little effect. Penile blood gas showed evidence of ischaemic priapism. The patient was transferred to a tertiary centre, where he underwent a penile aspiration, injection of further sympathomimetic, and corpora-spongiosum shunting under GA. Once back at the ward, he still had recurrent priapism. He was informed that he will have permanent damage and will need a penile implant. He was discharged and sent home with Co-amoxiclav and codeine, with a Urology outpatient follow-up in 4 weeks. Eventually, the patient underwent penile implantation, which 6 weeks later was complicated by penile abscess and required incision and drainage. This case report highlights the dangers of refractory ischaemic priapism following the concomitant use of recreational Viagra and cocaine. Concomitant drug abuse puts the patient at risk of full or partial penectomy, owing to possible failure of first-line management steps due to the propensity of cocaine to cause refractory priapism. Mechanisms of action of the drugs were described in this case report.